Trade and labour market outcomes: Theory and evidence at the firm and worker levels - Benjamin Aleman-Castilla (International Labour Organization (ILO), 2020)
The literature on the impact of trade on labour market outcomes has experienced a remarkable evolution in recent decades. Theory has moved on from oversimplified to more comprehensive models that take into account previously disregarded characteristics of firms and of product and labour markets, such as firm heterogeneity and labour market frictions. Thanks mainly to the availability of higher-quality data, greater computational capacity and improved econometric techniques, an increasing number of empirical studies provide valuable feedback that can be used for the continuous enhancement of the underlying theory. This working paper surveys the literature on the impact of international trade on firms and workers, presenting the main theoretical and methodological frameworks, including the assumptions on which these are based and the results obtained. It also discusses briefly the challenges that need to be addressed in future research, such as the collection of more and even higher-quality data, and the development of new statistical indicators that better reflect the dimensions of decent work.
Keywords: 330; decent work; labour market; workers; globalization; enterprises; trade liberalization; developed countries; developing countries